Home and School Influences on the Academic Performance of Students in Public Secondary School in Ogba/Egbema/Ndoni Local Government Area of Rivers State - Ogbonna-Martins Chinenye Ulunma (International Journal on Integrated Education, 2023)
This study investigated Home and school influences on the academic performance of students in public secondary schools in Ogba/Egbema/Ndoni Local Government Area of Rivers State. A descriptive survey design was adopted for the study. Four research questions guided the study. The population of the study comprised twenty (20) public secondary schools in the study area. The sample of the study was 400 students in public senior secondary schools drawn through a simple random sampling technique. An instrument structured by the researcher titled: “Home and School Influence and Students Academic Performance (HSISAP)” was used in collecting data for the study. The instrument yielded a reliability coefficient of 0.76. Mean and standard deviation were used in answering the research questions. The result of the findings showed that there is a positive influence on student’s academic performance based on the level of parents’ education. Based on the findings of the study, recommendations were made amongst others that Parents should give adequate attention to their children's activities at home and ensure that a good learning environment is maintained at home while suggestions for further studies were also stated.